2015
DOI: 10.1126/sciadv.1500078
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy rescues disease phenotype in a spinal muscular atrophy with respiratory distress type 1 (SMARD1) mouse model

Abstract: Preclinical proof-of-principle data demonstrate the high efficacy of IGHMBP2 gene therapy in the SMARD1 mouse model as well as in an in vitro model of the human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 26 publications
2
42
0
3
Order By: Relevance
“…Previous reports have shown that AAV9 vectors allow for a long‐term expression of the genes that they carry (Bernardes de Jesus et al ., ; Nizzardo et al ., ). To address whether AAV9‐TRF1 treatment allowed for long‐term TRF1 expression, we compared TRF1 mRNA and protein levels at the humane end point in our 2‐year‐old mouse cohort in which all mice had been already sacrificed.…”
Section: Resultsmentioning
confidence: 97%
“…Previous reports have shown that AAV9 vectors allow for a long‐term expression of the genes that they carry (Bernardes de Jesus et al ., ; Nizzardo et al ., ). To address whether AAV9‐TRF1 treatment allowed for long‐term TRF1 expression, we compared TRF1 mRNA and protein levels at the humane end point in our 2‐year‐old mouse cohort in which all mice had been already sacrificed.…”
Section: Resultsmentioning
confidence: 97%
“…The benefits obtained by the in vitro use of neurotrophic factors and pharmacological agents are not encouraging, 38,39 but better results have been obtained with the injection of rAAV in nmd mice. 32,48 The pathogenetic mechanisms underlying this disease are complex and not yet completely deciphered; in fact, mutations in the same IGHMBP2 gene can determine very serious (SMARD1) or mild phenotypes (CMT). Moreover, SMARD1 itself demonstrated substantial variability in terms of age of presentation, severity of the symptoms and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The factors Oct3/4, Sox2, c-Myc and Klf4 act together to overwhelm skin gene expression in fibroblasts and can activate genes encoding hESC proteins, thus inducing the reprogramming of somatic cells into iPSCs 28. Our group provided one of the first descriptions of the generation of IGHMBP2-mutated iPSCs from SMARD1 patients for in vitro studies of SMARD1 31,32. Our group provided one of the first descriptions of the generation of IGHMBP2-mutated iPSCs from SMARD1 patients for in vitro studies of SMARD1 31,32.…”
mentioning
confidence: 99%
“…Wirusy AAV wykorzystano w badaniach przedklinicznych m.in. w próbach leczenia przeponowej postaci rdzeniowego zaniku mięśni (SMARD1) [112]. Jak wspomniano wyżej, choroba spowodowana jest mutacjami w genie IGHMBP2 i dziedziczona w sposób autosomalny recesywny, podobnie jak CMT2S spowodowane mutacjami w tym samych genie [57].…”
Section: Próby Terapii Genowej W Cmtunclassified
“…Usprawnieniu uległy połączenia nerwowo-mięśniowe, a także wzrosła wielkość włókien mięśniowych. W hodowlach komórkowych uwidoczniono wyraźne zmniejszenie ubytku aksonów oraz ich wydłużenie [112]. Prowadzone badania u chorych ze SMARD1, stanowią również szansę na skuteczną terapię w przypadku chorych z CMT2S.…”
Section: Próby Terapii Genowej W Cmtunclassified